Decrease in Hospital Admissions for Acute Surgical Conditions During the COVID-19 Pandemic. Issue 2 (19th December 2020) - Paul, Subroto; Sesti, Joanna; Hilden, Patrick; Turner, Amber L.; Pencak, Dorothy; Anderson, Andy; Bonamo, John F.; Salemi, Arash
Abstract : Mini-Abstract: The nature of emergency room admissions for acute surgical conditions changed during the COVID-19 pandemic with less admissions for potentially life threatening conditions.